Pengaruh Harga, Store Atmosphere, Kualitas Produk, dan Pelayanan terhadap Kepuasan Pelanggan Lawless Burgerbar Kemang - Alvindra Taufik Pratama; Salsa Dilla; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Fast food, is a food with a fast-manufacturing process. According to the Statista website, the level of Indonesian people's fast-food consumption increased in 2018 to 36.81% of the total respondents. This shows that fast food is one type of food that is favored by all people. Researchers are interested in conducting research that aims to determine the effect of price, store atmosphere, product quality, and service quality, on customer satisfaction at Lawless Burgerbar Kemang. The sample of this study used a non-probability sampling sample of 125 customers at Lawless Burgerbar Kemang. This study uses primary data through distributing questionnaires to customers of Lawless Burgerbar Kemang. The data analysis technique uses multiple linear regression analysis, f-test and t-test using SPSS version 26. The conclusion of this study is that price has a positive and significant effect on customer satisfaction. Then store atmosphere, product quality, and service have no partial significant effect on customer satisfaction. Advice that can be given by Lawless Burgerbar Kemang should be to improve the quality of their product.